Morphometric characteristics of the knee are associated with the injury of the meniscus - Peixu Wang; Fuqiang Gao; Wei Sun; Zirong Li; Xinjie Wu; Lijun Shi; Xin Xu; Tengqi Li; Xiaoyu Fan; Chengxin Li; Zhizhuo Li (Journal of Orthopaedic Surgery and Research, 2022)
Abstract Background To assess the geometrical risk factors for meniscal injuries. We hypothesized that the narrowness of the intercondylar notch and the smaller tibial spine could increase the risk of meniscal injuries. Methods We retrospectively studied two hundred and seven patients examined for knee magnetic resonance images. Two experienced orthopedists evaluated the severity of meniscal injuries. The notch width, bicondylar notch width, notch width index, condyle width of the femur, tibial spine height, and intercondylar angle were measured in magnetic resonance image slides by two blinded orthopedists. Results A total of 112 patients with a meniscus injury and 95 patients were as healthy control in all two hundred and seven patients. The NWI (P = 0.027) in patients with meniscus injuries was significantly different from the control group. A 1 SD (0.04 mm) increase in NWI was associated with a 0.4-fold increase in the risk of meniscal injury. A 1 SD (0.04 mm) increase in NWI was associated with a 0.64-fold increase in the risk of grade 3 meniscal injury. Furthermore, NWI and medial spine height are decreased significantly in grade 2 (P < 0.05) meniscal injury than in other grades. The medial spine height was significantly decreased in the meniscal injury group (P = 0.025), and the decrease in medial spine height would increase the risk of meniscal injury (OR = 0.77) and grade 3 meniscal injury (OR = 0.8). Conclusions The stenosis of the femoral intercondylar notch and small medial tibial spine is risk factors of meniscal injury. The decreased NWI and the medial tibial spine height were also associated with the severity of the meniscal injury.